Pemberian Indole Acetic Acid dan Benzil Amino Purine Terhadap Pembentukan Protocorm dan Tunas Anggrek Vayes Limondok (Phaius tankervilleae (Banks) Bl ) In Vitro - Veronika L. Tuhumena (Fakultas Pertanian Universitas Papua, 2017)
The objective of this research is to identify the best combination of IAA and BAP concentration to support the formation of protocorms and budding of Phaius tankervilleae in vitro. This research were conducted with two treatment factors that are IAA and BAP concentration levels. The results showed that there were no interaction between IAA and BAP concentrations to the budding explant percentage and leaf number while they were affected by BAP concentration only. BAP concentration at 1 ppm produced the highest number of protocorm